Post-operative analgesic effects of butorphanol or firocoxib administered to dogs undergoing elective ovariohysterectomy - Camargo, Janaina Biotto [UNESP]; Steagall, Paulo V. M. [UNESP]; Minto, Bruno W. [UNESP]; Rodolfo de Sa Lorena, Silvia Elaine [UNESP]; Mori, Eduardo S. [UNESP]; Luna, Stélio Pacca Loureiro [UNESP] (Wiley-Blackwell, 2011)
ObjectiveTo compare the post-operative analgesic effects of butorphanol or firocoxib in dogs undergoing ovariohysterectomy.Study designProspective, randomized, blinded, clinical trial.AnimalsTwenty-five dogs > 1 year of age.MethodsDogs received acepromazine intramuscularly (IM), 0.05 mg kg-1 and either butorphanol IM, 0.2 mg kg-1 (BG, n = 12) or firocoxib orally (PO), 5 mg kg-1 (FG, n = 13), approximately 30 minutes before induction of anesthesia with propofol. Anesthesia was maintained with isoflurane. Ovariohysterectomy was performed by the same surgeon. Pain scores using the dynamic and interactive visual analog scale (DIVAS) were performed before and at 1, 2, 3, 4, 6, 8 and 20 hours after the end of surgery by one observer, blinded to the treatment. Rescue analgesia was provided with morphine (0.5 mg kg-1) IM and firocoxib, 5 mg kg-1 (BG only) PO if DIVAS > 50. Groups were compared using paired t-tests and Fisher's exact test (p < 0.05). Data are presented as mean +/- SD.ResultsThe BG required significantly less propofol (BG: 2.6 +/- 0.59 mg kg-1; FG: 5.39 +/- 0.7 mg kg-1) (p < 0.05) but the anesthesia time was longer (BG: 14 +/- 6, FG: 10 +/- 4 minutes). There were no differences for body weight (BG: 7.9 +/- 5.0, FG: 11.5 +/- 4.6 kg), sedation scores, and surgery and extubation times (BG: 10 +/- 2, 8 +/- 5 minutes; FG: 9 +/- 3, 8 +/- 4 minutes, respectively) (p > 0.05). The FG had significantly lower pain scores than the BG at 1, 2 and 3 hours following surgery (p < 0.05). Rescue analgesia was administered to 11/12 (92%) and 2/13 (15%) dogs in the BG and FG, respectively (p < 0.05).Conclusion and clinical relevanceFirocoxib produced better post-operative analgesia than butorphanol. Firocoxib may be used as part of a multimodal analgesia protocol but may not be effective as a sole analgesic.
Keywords: analgesia; butorphanol; dog; firocoxib; ovariohysterectomy